Determining of Obstacles to Total Quality Practicing at Accounting Department of Public Universities in Jordan - Khalil Alrifaaee; Akram Alnajdawi; Khalid Alkateeb (University of Science and Technology, Yemen, 2013)
Abstract: The overall objective of the study is to identify obstacles and problems faced by faculty members and administrators in the Divisions of Accounting and prevent the application of total quality management in public universities in Jordan. This has been reviewed in the first section of previous studies. In Section II the field study was conducted and included the hypothesis of the study. Meanwhile, the last Section has included a summary of results and recommendations emerging from the results.  -The main obstacles facing the application of total quality management in the accounting divisions in public universities of Jordan: 1. Weakness of financial support for scientific research. 2. The lack of objective criteria to measure performance. 3. Weak channels of communication between divisions and divisions of the university.